Research on the competitive situation and technical opportunities of global new textile materials technology R&D - Pengfei Wang; Hua Cheng (PLoS ONE, 2025)
Vigorously developing new textile materials technology is of great significance to improve the high-tech level of the textile industry, enhance the transformation and upgrading of the textile industry, promoting the sustainable development of the industry and the comprehensive national strength. This paper takes the 94,525 invention patents for new textile material technology in the world as the research object, and uses competitive situation calculation and patentometrics to explore the competitive situation, technical opportunities, and layout characteristics of technology R&D (Research and Development) in this field. The results show that the core patented technologies of the United States in the field of new textile materials are in a global leading position with a strong sense of overseas layout, which, like Japan, is more forward-looking than other countries and regions. The latter occupies a pivotal international position in a number of cutting-edge materials such as fibers, functional chemicals, and carbon fiber composites. Although China is a global patent major country, there is still a huge gap between the core patent R&D capabilities and the awareness of technical opportunities compared with developed countries such as the United States and Japan, which is the main problem that needs to be solved urgently in the future innovation and development, technology planning and layout of China’s textile industry. This study effectively supplement the theoretical analysis of competitive situation and technical opportunities of technology R&D, and enrich and expand the empirical research on international new textile materials technology and innovation.